Principal's Strategy for Increasing Interest in Foreign Languages at the Darunnajah Islamic Boarding School, Jakarta - Rokimin (Edukasiana: Journal of Islamic Education, 2023)
Principal's Strategy to Increase Interest in Foreign Languages ​​(Case Study of Darunnajah Islamic Boarding School) By holding several programs that support language improvement, students can find out their abilities and what to do to improve them, of course with support from the family and school environment. The method used is descriptive qualitative method with data collection techniques in the form of observation, interviews and documentation. Sources of informants included school principals, teachers, English program supervisors, and students. Data analysis activities in the form of data reduction, data presentation as well as conclusion and verification. In testing the validity of the data, the researcher extended the research time, triangulation, and member checking. Based on the results of the research, it is known that there are several special programs that are the principal's strategy in increasing students' interest in language.